2016
DOI: 10.1111/ggi.12749
|View full text |Cite
|
Sign up to set email alerts
|

Too little sleep and too much sleep among older adults: Associations with self‐reported sleep medication use, sleep quality and healthcare utilization

Abstract: Sleep medication use does not appear to promote sleep health. Both short and long sleep durations are associated with a higher likelihood of healthcare use. Clinicians need to examine older adults' sleep health and medication use, and their effects on healthcare use. Geriatr Gerontol Int 2017; 17: 545-553.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…7 Both shorter and longer sleep durations relative to these recommendations have been associated with increased incidence of cardiovascular disease, diabetes mellitus, stroke, and allcause mortality. [8][9][10][11][12] Because sleep plays an important role in the regulation of inflammatory responses, adverse health outcomes from poor quality or short sleep are believed to be associated with increased systemic inflammation. 13 The nature of the association between long sleep duration and increased mortality risk remains poorly understood, and it is unknown whether these associations are causal or modifiable.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Both shorter and longer sleep durations relative to these recommendations have been associated with increased incidence of cardiovascular disease, diabetes mellitus, stroke, and allcause mortality. [8][9][10][11][12] Because sleep plays an important role in the regulation of inflammatory responses, adverse health outcomes from poor quality or short sleep are believed to be associated with increased systemic inflammation. 13 The nature of the association between long sleep duration and increased mortality risk remains poorly understood, and it is unknown whether these associations are causal or modifiable.…”
Section: Introductionmentioning
confidence: 99%
“…14 Restorative sleep is now recognized as essential for physical, cognitive, and psychological well-being across the life span. 4,9,13,[15][16][17] Sleep itself is an important behavioral risk factor for worsening pain, depression, anxiety, and chronic conditions, perpetuating both sleep problems and poor health outcomes. Thus, unresolved sleep problems have far-reaching consequences on physical and mental health among older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that ICU patients experience poor sleep quality (Shiung et al, ; Pisani et al , ), possibly because of frequent treatment, continuous light exposure, noise from equipment and ambient noise in an emergency, mechanical ventilation, medication side effects and their disease conditions (Boyko et al , ). Insufficient sleep among critically ill patients can have adverse catabolic effects and negatively impact recovery, thus extending hospitalization durations and increasing medical costs (Xu et al , ; Choi et al, ). Poor sleep quality has been shown to be associated with a higher likelihood of health care use (Choi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient sleep among critically ill patients can have adverse catabolic effects and negatively impact recovery, thus extending hospitalization durations and increasing medical costs (Xu et al , ; Choi et al, ). Poor sleep quality has been shown to be associated with a higher likelihood of health care use (Choi et al, ). Moreover, the impact of poor sleep quality on health appears to remain after discharge from the ICU (Altman et al, ).…”
Section: Introductionmentioning
confidence: 99%